PHYSICAL QUALITY OF RACE CHICKEN EGGS SOLD BY CAR TRADERS IN THE TIME OF THE COVID-19 SKILLS IN DENPASAR - Y. H., Langambani; Sutama, I N. S.; Umiarti, A. T. (Jurnal Peternakan Tropika, 2023)
This study aims to determine whether the physical quality of purebred chicken eggs sold by car dealers during the Covid-19 pandemic in Denpasar is still suitable for consumption. The research was conducted in April 2022 at the Laboratory of Animal Products Technology, Faculty of Animal Husbandry, Udayana University Jl. Sudirman Denpasar. This study used a completely randomized design (CRD) with four treatments and three replications. The four treatments were: eggs taken from car dealers in East Denpasar (DT), West Denpasar (DB), South Denpasar (DS) North Denpasar (DU). Each replication used 10 eggs from each treatment with a homogeneous weight. The observed variables were egg weight, Haugh unit (HU), acidity (pH), yolk index, albumin index, and shell thickness. The results of this study indicate that eggs from the treatment of East Denpasar, Denpasar Barar, South Denpasar and North Denpasar, experienced a decrease in physical quality but were still within the range of the 2008 National Standardization Agency. unit, acidity, yolk index and albumin index from East Denpasar West Denpasar, South Denpasar and North Denpasar decreased physically, but still within the range of the National Standardization Agency, 2008. So that eggs sold by car swords are still fit for consumption.